MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII - Pratiwi, Widya Chandra; Kusdianah, Kusdianah; Susanah, Susanah (Universitas Tribhuwana Tunggadewi, 2023)
This research aims to improve students' mathematics learning outcomes by using Project Based Learning (PjBL). This study used 2 cycles of PTK with the subject of 33 grade VII students at SMPN 2 Surabaya through four stages, namely Plan, Action, Observe, and Reflect. Each cycle consists of three meetings using teaching modules, student worksheets (LKPD), test questions, student activity observation sheets and also learning implementation observation sheets. The results showed that there was an increase in learning outcomes with an average of 73.18 in the first cycle to 81.21 in the second cycle, in addition, class completeness also increased from 42.42% to 84.84%. This shows that the Project Based Learning (PjBL) learning model can improve students' mathematics learning outcomes.